Dispersal syndromes of the natural regeneration of a “Cerrado” sensu stricto area and two eucalyptus clones understory, Aliança-TO: Dispersal syndromes of the natural regeneration of a “Cerrado” sensu stricto area and two eucalyptus clones understory, Aliança-TO (Élisée - Revista de Geografia da UEG, 2021)
The objective of this work was to characterize the natural regeneration of an area of ​​cerrado sensu stricto (css) and undergrowth of two stands of Eucalyptus urocam (E. uc) and Eucalyptus urograndis (E. ug), as well as to compare the syndromes of diaspore dispersal, the succession of ecological groups and the classification into peculiar and accessory species. This study was conducted in the rural area of ​​Aliança - TO, within the boundaries of the Nossa Senhora Aparecida property (11 ”46'25 S; 49” 02'54 W). The species were classified by zoocoric, anemochoric, autocorric dispersal syndrome and in the ecological groups, classifying them as pioneer (P), early secondary (Si) and late secondary (St) and unidentified (Ni). accessory or peculiar species. In the three areas studied there was a predominance of zoochoric species (55.4%, 70% and 63%), followed by anemochoric species (37.5%, 20% and 29.6%) and finally the autochoric species (7.1%, 10% and 7.4%), assimilating a strong relationship between the fauna and the local community. Regarding the ecological groups of the sectional classification, the group of pioneers and early secondary was the most outstanding (67.8% in css, 70% in E. uc and 69.6% in E. ug), characterizing areas in stage initial succession. By classifying the species as peculiar and accessory it was found that in the studied areas the occurrence of the species considered exclusively or expressively of the Cerrado biome prevailed.